Cost And Time Management In The Agrifood Supply Chain: A Case Study Of The Papaya Supply Chain At MAFC (Malaysia Agrifood Corporation Berhad) - Noormohamed, Fezan Mohamed (2010)
This project has applied the Supply Chain Time and Cost Mapping (SCTCM) toolkit which uses Time-Cost analysis. The SCTCM tools have been successfully developed in the UK under the Supply Chain Cost Effectiveness and Swift Service (SUCCESS) research project. The SUCCESS programme which was initiated in 2001, aimed at “developing a diagnostic toolkit that could provide visibility of cost and waste in the supply chain” by combining “the elements of time-based methodologies and activity-based costing techniques”. Previous application of SCTCM in industry has shown that a non-linear relationship exists between cost and time in processes. The project explored issues relevant to the fresh produce supply chain and analyzed a case study on the papaya fruit at a local Malaysian company called the Malaysian Agrifood Corporation Berhad (MAFC), which is an integrated food supply chain company focusing on fresh produce. The project involved collaborating with the MAFC employees to carry out the Process mapping and Activity-Based Costing techniques on the supply chain to highlight areas which consume large amount of processing time and costs. Subsequently, possible areas of improvement and time and cost saving opportunities have been recommended.